2020
DOI: 10.1039/c9ta11341j
|View full text |Cite
|
Sign up to set email alerts
|

A dual-salt coupled fluoroethylene carbonate succinonitrile-based electrolyte enables Li-metal batteries

Abstract: We report a novel succinonitrile (SN)-based electrolyte SN–DLi–FEC (SN–LiTFSI–LiODFB–FEC), which shows excellent compatibility with the Li-metal anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 35 publications
4
77
0
Order By: Relevance
“…By contrast, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC) are effective in forming a benign and robust SEI on the lithium surface . Due to its relatively high solvating power and ready availability, FEC has been selected as the SEI enabler by many researchers all over the world . Although FEC‐based electrolytes are widely used in LMBs, a detailed solvation study has not been reported due to the difficulty in characterizing the solvation status of FEC by vibrational spectroscopy .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC) are effective in forming a benign and robust SEI on the lithium surface . Due to its relatively high solvating power and ready availability, FEC has been selected as the SEI enabler by many researchers all over the world . Although FEC‐based electrolytes are widely used in LMBs, a detailed solvation study has not been reported due to the difficulty in characterizing the solvation status of FEC by vibrational spectroscopy .…”
Section: Figurementioning
confidence: 99%
“…[27,31,32] Due to its relatively high solvating power [33] and ready availability, FEC has been selected as the SEI enabler by many researchers all over the world. [27,[31][32][33][34][35][36][37][38][39] Although FEC-based electrolytes are widely used in LMBs, a detailed solvation study has not been reported due to the difficulty in characterizing the solvation status of FEC by vibrational spectroscopy. [33] Yet, it is crucial to understand the solvation state to develop a reliable electrolyte system for LMBs.…”
mentioning
confidence: 99%
“…A recent study reported similar color change phenomenon of SN by placing Li metal in this solvent. [ 39 ] Thus, the SN content is significantly reduced to 1% in the PEO membrane (PEO‐LiTFSI‐1% SN, denoted as PEO‐1% SN) to minimize any undesired side reactions.…”
Section: Resultsmentioning
confidence: 99%
“…4,12,13 As a potential candidate of the electrolyte solvent component, succinonitrile (SN) with thermal stability and high oxidation resistance has been reported as a versatile electrolyte additive to improve the thermal stability and extend the voltage window of various electrolytes. 14,15 As an effective electrolyte additive, the SN can be applied to alleviate the interface oxidation process between the entire electrolyte system and high-voltage cathodes by coordinating with metal ions on cathodes, thus reducing the undesirable side reaction between the electrolyte and the electrodes and, nally, protecting the high-voltage cathodes. 16 It is worth noting that SN has also been employed as an effective plasticizer to enhance the ionic conductivity and electrochemical stability of solid-state/quasisolid-state polymer electrolyte systems due to its high polarity and plastic-crystalline conformation property.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, owing to its high polarity and dielectric constant (3 ¼ 55, at 25 C) but relatively low melting point (54-62 C), SN has demonstrated its favorable solubility towards various lithium salts, and is regarded as an efficient electrolyte solvent in preparing multiple electrolytes. 14 In brief, as shown in the right part of Fig. 1a, these remarkable advantages make SN a promising lithium-ion transfer medium in preparing dilute and/or solidstate electrolytes for lithium-metal battery systems.…”
Section: Introductionmentioning
confidence: 99%